HOTEL UNIK BERKRITERIA KHUSUS STUDI KASUS HOTEL AMANJIWO - Mita Mariska; Yuke Ardhiati; Yusuf Affendi Djalari (Universitas Trisakti, 2014)
AbstractThe ever-increasing level of competition in the hospitality world of has given birth to a new type of hotel, one that cannot be simply classified using the exiting star rating system. Such hotels are not considered as facilitating as most hotels, but they are designed neatly, each with a theme that correspondens to the local genius. These hotel are often called